PELATIHAN INTEGRASI BUDAYA LOKAL UNTUK MENINGKATKAN PSYCHOLOGICAL WELL-BEING SISWA SEKOLAH MENENGAH ATAS DI KABUPATEN PONOROGO - Ari Khusumadewi; Budi Purwoko; Titin Indah Pratiwi; Asieline Wahyu Tri Ardyanti; Mila Yunita; Dimas Ardika Miftah Farid; Farah Nikmatus Sania; Zara Diva Paramatatwa; Dyah Amelia Susanti (Universitas Negeri Surabaya, 2026)
Strengthening students' psychological well-being is an important topic in secondary education, especially in areas with rich local culture, such as Ponorogo Regency, which is famous for its local culture, Reog Ponorogo. This community service activity aims to improve the competence of guidance and counseling teachers in developing and implementing culture-based guidance and counseling services as an effort to improve the psychological well-being of high school students. The implementation method included training and mentoring for 30 guidance and counseling teachers who are members of the MGBK SMA Ponorogo Regency through workshops, discussions, live models, and practice in developing guidance and counseling service modules independently. The results showed that the majority of participants demonstrated increased understanding and skills in integrating local cultural potential into guidance and counseling services. The results of the pre-test and post-test showed that 98.67% of participants reported benefiting from the training, 72% of participants reported that the material presented was easy to understand, 97.33% of participants reported that the methods used were appropriate, and 98.67% of participants reported that the training helped improve their competencies. This training has proven to have a significant impact in positively contributing to the strengthening the competence of guidance and counseling teachers in supporting students' psychological well-being through a contextual service approach based on local culture.